P-063 Psychosocial Burden Among Patients with IBD: Prospectively Collected Data from 2 Academic Institutions. (March 2016) - Atreja, Ashish; Szigethy, Eva; Colombel, Jean-Frédéric; Otobo, Emamuzo; Ullman, Thomas; Marion, James; Rogers, Jason; Itzkowitz, Steven; Riaz, Muhammad; Chapman, Mark; Cohen, Benjamin; Grinspan, Ari; et al.
Abstract : Background: Inflammatory Bowel Disease (IBD) is a chronic condition of the bowel that affects over 1.5 million people in the United States. The recurring nature of disease makes IBD patients' ideal candidates for patient-engaged care that is centered on enhanced self-management and improved doctor-patient communication. Thus the HealthPROMISE App was developed which is a unique cloud based PRO (patient reported outcomes) and decision support tool that empowers both patients and providers with a more comprehensive and continuous assessment. The App is implemented at 5 academic centers and undergoing pragmatic clinical trial at Mount Sinai Medical Center. Methods: Participants are being recruited after informed consent is obtained during face-face visits and are then randomized to either an interventional (i.e., HealthPROMISE) or control (i.e., education app) group. Patients in the HealthPROMISE arm are able to update their information and receive disease summary, quality metrics and a graph showing the trend of quality of life (SIBDQ) scores and resource utilization over time. Data is being collected in real time using the HealthPROMISE app from IBD patients at Mount Sinai and compared with paper-based surveys from patients at University of Pittsburgh Medical Center. SIBDQ scores are being generated and analyzed to look into psychosocial domains. Results: Of the 200 patients enrolled in the study at Mount Sinai Medical Centers, 102 were randomised to the intervention group and 98 to the control group (Females, 49.5%; White, 82.0%; Black, 11%; Hispanics, 9.5%; English as primary language, 96%; Everyday Computer Usage, 93%). When we analyzed the baseline data from both academic centers, we found striking similarity between prospectively collected data at UPMC on paper (n = 1543) with electronic data collected in real time from HealthPROMISE app in the last 5 months (N = 200). Both show fatigue and tension (anxiety) as major drivers of poor quality of life in more than 75% of patients with IBD. Overall, Psychosocial domains (Tension, Fatigue, Pain and Angry) were top 4 domains driving poor quality of life. Gastroenterology specific domains such as Bathroom issues and Weight maintenance were overall in good or fair control in majority of patients (>64%). In addition to comparative data between the 2 institutions, we will be presenting longitudinal data on overall quality of life and psychosocial domains among interventional patients in ongoing clinical trial. Conclusions: IBD patients need continuous assessment of psychosocial distress as they are the major contributing factors to poor quality of life. Interventions focused on improving stress and fatigue will be required to improve patients' well being and quality of life.